2019
DOI: 10.3390/md17010043
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of a Chitosan Oligosaccharide-Streptomycin Conjugate against Pseudomonas aeruginosa Biofilms

Abstract: Microbial biofilms are considerably more resistant to antibiotics than planktonic cells. It has been reported that chitosan coupling with the aminoglycoside antibiotic streptomycin dramatically disrupted biofilms of several Gram-positive bacteria. This finding suggested the application of the covalent conjugate of antimicrobial natural polysaccharides and antibiotics on anti-infection therapy. However, the underlying molecular mechanism of the chitosan-streptomycin conjugate (CS-Strep) remains unclear and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Interestingly, it was thought that gallic acid in the chitosan conjugate does not exert major antibacterial activity, and there may be synergistic effects of phenolic acid and CS through conjugation [115]. Similar results have also been reported by two other labs [37,86], suggesting that the coupling of chitosan and streptomycin may play a synergistic effect. In general, chitosan conjugates generally have a broader spectrum and higher antimicrobial activity than chitosan.…”
Section: Physiochemical Properties and Antimicrobial Activitiessupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, it was thought that gallic acid in the chitosan conjugate does not exert major antibacterial activity, and there may be synergistic effects of phenolic acid and CS through conjugation [115]. Similar results have also been reported by two other labs [37,86], suggesting that the coupling of chitosan and streptomycin may play a synergistic effect. In general, chitosan conjugates generally have a broader spectrum and higher antimicrobial activity than chitosan.…”
Section: Physiochemical Properties and Antimicrobial Activitiessupporting
confidence: 73%
“…It has been reported that galactose [82], curcumin [35], inulin [83], and caffeic acid [84] can be successfully coupled with chitosan to obtain the corresponding conjugates by this method. It should be noted that, considering the instability of the Schiff base, the chitosan Schiff base conjugate is usually reduced to a stable amino-substituted chitosan conjugate through sodium borohydride or sodium cyanoborohydride [37,85,86].…”
Section: Coupling By Forming a Schiff Basementioning
confidence: 99%
“…This approach has already been used with streptomycin, where the conjugate, COS-Strep, was proven to decrease PA biofilm mass more effectively than the unconjugated components alone or mixed. [157] Interestingly…”
Section: Recent Development Of Anti-infective Delivery Systems For Trmentioning
confidence: 99%
“…Anti-pseudomonal drugs such as ciprofloxacin 103ā€“ 105 , meropenem 106 , tobramycin 107, 108 , gentamicin 109 , or amikacin 110 were encapsulated into liposomes or loaded into nanoparticles. The drug delivery systems were diverse in chemical nature and include anionic liposomes 105, 106, 109 , poly(lactic-co-glycolic) acid nanoparticles 110, 111 , water-soluble chitosan oligosaccharide conjugates 112 , oil-in-water cross-linked polymeric nanocomposites 113 , graphen-oxide conjugates 107 , or solid lipid nanoparticles 114 , to name just a few. Alternatively, dry powders 103, 104, 108, 115 or hydrogels 116ā€“ 119 were formulated or wound dressings were coated with a topical antimicrobial such as silver oxynitrate 120 .…”
Section: Novel Formulations For Anti-pseudomonal Drug Deliverymentioning
confidence: 99%